Some scholarly communication guidelines - Cortez, Paulo (2011)
Scholarly communication describes the process of sharing and publishing of research findings. This report provides some useful guidelines for improving a key scholarly communication aspect: the writing of scientific documents (e.g. journal articles, conference papers, Doctor of Philosophy thesis). The goal is to have a written text to complement both a two hour seminar, given under the same subject and that was presented to Computer Science students, and the ``Scholarly Communication'' course unit, lectured for Information Systems students. For further reading purposes, this report includes an additional list of references related with other aspects of scholarly communication (e.g. designing scientific presentations).